PENGARUH CURRENT RATIO (CR) DAN DEBT TO ASSET RATIO (DAR) TERHADAP NET PROFIT MARGIN (NPM) PADA PT ASTRA INTERNATIONAL, TBK PERIODE 2014-2023 - Moh Farhanudin; Tri Wartono (Journal of Research and Publication Innovation, 2025)
This research was conducted at PT Astra International Tbk, which is a company operating in the automotive sector. The aim of this research is to determine the influence of the Current Ratio (CR) and Debt to Asset Ratio (DAR) on Net Profit Margin (NPM) at PT Astra International, Tbk for the 2014-2023 period, both individually and simultaneously. This type of research is descriptive and the research method used is a quantitative method with the sample used in this research coming from annual financial reports for the last 10 years, namely from 2014 to 2023. This will explain the relationship between the independent variable and the dependent variable. . Data analysis used includes: Curren Ratio, Debt to Asset Ratio and Net Profit Margin, descriptive test, classical assumption test, multiple linear regression test and hypothesis test (t test and F test) with a significance level of 0.05 (5%) and The data source used is secondary data. The results of this research show that the Current Ratio (CR) has a significant effect on Net Profit Margin (NPM), this is proven by (t test) that the value of tcount (6.144) > ttable (2.36462) with a significance value of (0.000) < ( 0.05). The results of this research show that the Debt to Asset Ratio (DAR) has a significant effect on Net Profit Margin (NPM), this is proven by (t test) that the value of tcount (7.891) > ttable (2.36462) and the significance value (0.000) < (0.05). Simultaneous testing shows that the Current Ratio (CR) and Debt to Asset Ratio (DAR) simultaneously have a significant effect on Net Profit Margin (NPM), this is proven by (F test) that the Fcount value is 31.361 > Ftable 4.74 with a significant level 0.000 > 0.05.